Improving Underachiever Students' Mathematics Learning Outcomes: The Effectiveness of the STAD Model - Savitri Suryandari (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
This study aims to obtain an objective picture of the effect of the Student Team Achievement Division (STAD) type cooperative learning model on mathematics learning outcomes in underachievers. This research is an actual experiment with a randomized pretest-posttest control group design. The sample of this study consisted of two classes, namely the experimental class and the control class, with a total of 30 people, each determined by random sampling technique. The data analysis technique used is the t-test. The results of this study indicate that the mathematics learning outcome obtained on average in the experimental group is 39.633, while in the control group is 27.267. This means that learning outcomes using the STAD method are better than mathematics learning outcomes using conventional models. The high average score in the experimental group positively affected the testing of hypotheses performed using the t-test